Abnormalities in renal tubular phosphate handling in children with sickle cell disease. Issue 12 (17th August 2014) - Raj, Vimal Master Sankar; Freundlich, Michael; Hamideh, Dima; Alvarez, Ofelia; Seeherunvong, Wacharee; Abitbol, Carolyn; Katsoufis, Chryso; Chandar, Jayanthi; Ruiz, Phillip; Zilleruelo, Gaston
<x xml:space="preserve">Abstract</x> Background The mechanisms responsible for the hyperphosphatemia in patients with sickle cell disease (SCD) and preserved glomerular filtration rate (GFR) are not fully understood. The role of fibroblast growth factor 23 (FGF23), a phosphaturic hormone has not been investigated in SCD. Hence, we evaluated parameters of renal tubular phosphorus handling and their relation to prevailing FGF23 levels in a cohort of young SCD patients. Methods Renal tubular phosphate handling and circulating levels of various analytes including FGF23 and parathyroid hormone (PTH) were measured in 24 children with SCD and normal estimated GFR in a cross sectional study. Correlation and regression analysis were employed to derive relationships between serum phosphorus and several variables. Results Most children showed elevated age‐ adjusted serum phosphorus (5.1 ± 0.7 mg/dl) levels. Tubular re‐absorption of phosphorus(TRP) (96.3 ± 2.1%) and tubular maximum re‐absorption of phosphorus per unit volume of GFR (TMP/GFR) (4.9 ± 0.6 mg/dl) were both elevated. Plasma intact FGF23 concentrations were elevated (81 ± 38 pg/ml) while the average PTH values were normal in most patients (50 ± 27 pg/ml). Univariate analysis showed significant correlations of serum phosphorus with TMP/GFR, alkaline phosphatase, age, lactate dehydrogenase (LDH), and log intact FGF23. TMP/GFR correlated with log intact FGF23 (r = 0.5, P< or = 0.01) but not with PTH. Multiple regression analysis yielded an independent relationship of serum phosphorus with TMP/GFR. Conclusion The elevated serum phosphorus concentrations with simultaneously increased TMP/GFR and elevated FGF23 levels collectively suggest that patients with SCD display proximal tubular resistance to the action of FGF23 before any decline in GFR. Pediatr Blood Cancer 2014;61:2267–2270. © 2014 Wiley Periodicals, Inc.